Tubular composites of quartz glass and methods of production and use thereof

By adopting OVD external deposition method and high viscosity quartz glass base tube in the production of quartz glass tubular composites, the problem of maintaining the shape of soot body in the production of large-size quartz glass cylinders is solved, and the large-size quartz glass tubular composites is realized. Reproducible production and dimensional stability.

CN119461877APending Publication Date: 2025-02-18HERAEUS QUARZGLAS GMBH & CO KG
View PDF 6 Cites 0 Cited by

Patent Information

Application Number
CN202411017519.0
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Priority Date
2023-08-08
Filing Date
2024-07-26
Publication Date
2025-02-18

AI Technical Summary

Technical Problem

When producing large-size quartz glass cylinders, the soot to be sintered becomes difficult due to the increase in weight and the temperature difference between the inside and outside, and it is difficult to reliably maintain the shape of the soot body, and waste is easily generated.

Method used

The outer deposition method, especially the OVD outer deposition method, is used to produce a quartz glass tubular composite with large inner diameter and wall thickness. By using a base tube of first quartz glass quality with high viscosity and a soot body of second quartz glass quality, it is ensured that the base tube provides sufficient support during the sintering process to avoid soot body collapse and waste generation.

Benefits of technology

Reproducible production of large-size quartz glass tubular composites is achieved, reducing the risk of waste and improving the dimensional stability of the product.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119461877A_ABST
    Figure CN119461877A_ABST
Patent Text Reader

Abstract

A known method for producing a tubular quartz glass composite in an extrinsic deposition method comprises the following method steps: providing a substrate tube; rotating the base tube about an axis of rotation; depositing SiO2 particles on the outside surface of the substrate tube to form a composite material consisting of the substrate tube and a SiO2 soot body; and sintering the composite material by heating at a sintering temperature to form the tubular quartz glass composite. In order to enable reproducible production of a tubular composite of quartz glass having a particularly large inner diameter of more than 200 mm and a wall thickness of more than 25 mm, it is proposed that a base tube at least partially consisting of quartz glass of a first quartz glass quality is provided, and that the soot body consists of quartz glass of a second quartz glass quality, wherein the material specific viscosity of the first quartz glass quality at the sintering temperature is higher than the material specific viscosity of the second quartz glass quality.
Need to check novelty before this filing date? Find Prior Art

Description

Background Art

[0001] The invention relates to a composite body of quartz glass, in particular a tubular composite body of quartz glass having a green wall, a length of at least 1,000 mm and an inner diameter of at least 250 mm.

[0002] The invention also relates to the production of a tubular quartz glass composite body, in particular to a method for producing a tubular quartz glass composite body by an external deposition method, the method comprising the following method steps:

[0003] (a) providing a substrate tube having a continuous through hole, a substrate tube outer diameter, a substrate tube inner diameter, a substrate tube wall thickness, a substrate tube outer side surface and a substrate tube inner side surface, wherein the continuous through hole extends coaxially with a longitudinal axis of the substrate tube,

[0004] (b) rotating the substrate tube about an axis of rotation extending coaxially or parallel to the longitudinal axis of the substrate tube,

[0005] (c) depositing SiO2 particles on the outer surface of the substrate tube by at least one deposition burner to form a composite material consisting of the substrate tube and the SiO2 soot body,

[0006] (d) sintering the composite material by heating at a sintering temperature to form a tubular quartz glass composite body.

[0007] Quartz glass components in the form of preforms, tubes, rods, flanges, plates, rings, reactors, crucibles, etc. are used in semiconductor production and in the manufacture of optical fibers. Such components are usually produced from tubular semi-finished products of quartz glass by hot forming and / or mechanical treatment thereof. With increasing production rates, larger dimensions of such components are increasingly sought, which are associated with larger wall thicknesses and inner diameters, especially in the case of tubular semi-finished products.

[0008] In order to produce tubular semi-finished products from synthetically produced silicon dioxide, a CVD method (chemical vapor deposition) is known, in which SiO2 particles are deposited on a substrate from the gas phase. The CVD external deposition method, abbreviated as "OVD" (external vapor deposition), is generally suitable for producing large-volume semi-finished products. In this process, the silicon-containing starting material is converted into SiO2 particles by flame hydrolysis or pyrolysis in a reaction zone, and these particles are deposited in layers on the outer jacket of a cylindrical substrate rotating around its longitudinal axis. The reaction zone is generated by a heat source, in which the longitudinal axis of the substrate and the heating source move back and forth relative to each other. The substrate can be tubular and is also referred to as a "substrate tube" here and below. The substrate tube is, for example, composed of quartz glass, SiC, SiSiC (reaction bonded silicon carbide), Al2O3 or other ceramic materials or graphite, and is fixed and rotated around its longitudinal axis by a lathe-like device (also referred to as a "substrate tube holder" here).

[0009] Depending on the temperature during the deposition process, the synthetic SiO2 layer deposited on the substrate tube is still porous and is also referred to below as a "soot layer" or "soot body", or it forms a dense layer of more or less transparent quartz glass. In the case of a porous soot layer, this body is sintered in a separate process step to form more or less transparent quartz glass (the sintering process is also referred to as "vitrification"). From the tubular quartz glass semi-finished product produced in this way, synthetic quartz glass components such as solid cylinders, hollow cylinders or parts of these components are obtained by mechanical, chemical and / or thermal aftertreatment, which components themselves can also be used as semi-finished products for producing other components.

[0010] Prior art

[0011] US 8,316,671 B2 describes an OVD external deposition method for producing hollow cylindrical bodies of quartz glass. A substrate tube of quartz glass is provided and a porous SiO2 soot layer is deposited on its outer surface. The composite material consisting of the substrate tube and the SiO2 soot layer is vitrified in such a way that the interior of the substrate tube remains below the deformation temperature. For this purpose, the inner bore of the substrate tube can be cooled by gas or liquid during the vitrification process. The inner wall of the tubular composite body of quartz glass produced in this way is formed by the substrate tube; it is smooth and no longer needs to be mechanically processed.

[0012] From US 2013 / 115391 A1, a method for producing a hollow quartz glass cylinder with a large outer diameter is known, in which a porous soot body of silicon dioxide soot is deposited on a substrate using an OVD external deposition method. After the substrate is removed, the soot body is sintered to form a hollow cylinder. Rings are thereby sawn, which consist of quartz glass with a low chlorine content and at the same time a low hydroxyl group content and therefore have a high viscosity. The quartz glass rings are used as so-called "plasma etching rings" to hold semiconductor wafers in plasma etching systems.

[0013] For vitrification of the soot body, the soot body is held in a sintering furnace with its longitudinal axis aligned vertically or horizontally. If the longitudinal axis is aligned vertically, the soot body can be vitrified standing on a platform. However, there is a risk that the soot body will deform due to its weight and collapse. A caterpillar-like structure consisting of circumferential folds may form, so that the dimensional accuracy requirements cannot be met; in particular, the specified minimum inner diameter may be exceeded.

[0014] The method known from EP 701975 A2 avoids some of these disadvantages. A tubular soot body is introduced into a vitrification furnace and held therein in a vertical orientation by a holding device, which comprises a holding rod which extends from above through the inner bore of the soot body and is connected to a holding foot on which the soot body initially stands with its lower end. The holding rod consists of carbon fiber reinforced graphite (CFC) and is tightly covered by a gas-permeable, thin-walled cladding tube of pure graphite. In a position above the upper end of the cladding tube, a graphite support ring is embedded in the inner bore of the soot body and protrudes from the soot body wall inwardly into the soot body inner bore.

[0015] During vitrification, the soot body is moved zone by zone from its upper end through the annular heating element. The soot body gradually collapses onto the graphite cladding tube and also shrinks in length, so that in the first sintering stage, the soot body stands upright on the retaining feet. The position of the graphite support ring embedded in the soot body is selected so that the graphite support ring is supported on the graphite cladding tube in the second sintering stage due to the increase in longitudinal shrinkage, so that the soot body is then kept suspended at the upper end. This method is also referred to below as "suspended vitrification". After vitrification, the cladding tube is removed and the inner bore of the resulting quartz glass tube is finished by drilling, grinding, honing or etching.

[0016] In order to reduce the graphite contact surface, in a modification of the method according to DE 103 03 290 B3, a sleeve of synthetic quartz glass is arranged between the holding rod and the soot body to be vitrified. The production of such a sleeve requires a lot of time and money and is the quartz glass tube or forms part of the quartz glass tube.

[0017] In the method known from DE 100 64 730 A, SiO2 particles are deposited on an elongated substrate tube which is rotated about its longitudinal axis and whose outer diameter has a gradient over its length. After the stepped substrate tube is removed, a porous hollow cylindrical soot body is obtained, the inner bore of which has a complementary shape corresponding to the outer diameter profile of the substrate tube, i.e. it has a stepped shoulder. The soot body obtained in this way is suspended in a furnace for vitrification in a vertical orientation, wherein the narrowing region of the inner bore is arranged at the top and the holding rods which protrude from above into the inner bore reach below the stepped shoulder. A relatively wide shoulder of the inner bore is required for reliable holding of heavy soot bodies.

[0018] Technical goals

[0019] As quartz glass cylinders become larger and larger, the weight of the soot body to be sintered and the increasing temperature difference between the inside and outside make the production method more difficult. With the above-mentioned procedure, it is problematic to reliably hold the heavy soot body during vitrification and to produce quartz glass tubes reproducibly. In particular, the generation of waste in the later stages of the method, such as when vitrifying the soot body, should be avoided.

[0020] Similar problems also arise when vitrifying other porous SiO 2 bodies which have not been produced via the SiO 2 soot route, for example using porous SiO 2 bodies obtained via the known sol-gel route or by pressing methods.

[0021] It is therefore an object of the present invention to specify a method for producing such a large-volume tubular composite body of quartz glass using an external deposition method, in particular using an OVD external deposition method.

[0022] In particular, the object of the present invention is to provide a method for the reproducible production of tubular composite bodies of quartz glass having a large inner diameter, in particular having an inner diameter of more than 200 mm and a wall thickness of more than 25 mm, according to an external deposition method, which method avoids the above-mentioned disadvantages and in which in particular the risk of waste generation is reduced.

[0023] Furthermore, the object of the present invention is to provide a tubular quartz glass composite body which is characterized on the one hand by large dimensions, and in particular by an inner diameter of more than 200 mm, a wall thickness of more than 25 mm and a length of at least 1,000 mm, while at the same time also by high dimensional stability. DETAILED DESCRIPTION

[0024] With regard to a method for producing a tubular composite body of quartz glass, the object is achieved according to the invention starting from a method of the type mentioned at the outset in that a substrate tube is provided which at least partially consists of quartz glass of a first quartz glass quality, and the soot body consists of quartz glass of a second quartz glass quality, wherein the material-specific viscosity of the first quartz glass quality at the sintering temperature is higher than the material-specific viscosity of the second quartz glass quality.

[0025] The method comprises the following method steps: A porous soot body of synthetic silicon dioxide SiO2, also referred to hereinafter as "soot body", is produced using an external deposition method, in particular an OVD external deposition method. The porous SiO2 soot body can optionally be subjected to a dehydration treatment in an inert gas, a chlorine-containing gas or under vacuum to reduce the hydroxyl group content of the quartz glass and is then sintered to form more or less transparent quartz glass. Sintering (or vitrification) takes place, for example, under vacuum or in an atmosphere containing helium and / or hydrogen and / or nitrogen.

[0026] The substrate tube is designed to produce a SiO2 soot body with a large inner diameter on its outer surface using an external deposition method. For example, the substrate tube has a substrate tube length of up to 4 m and is cylindrical, conical or stepped over its entire length or part of its length. The inner profile is constant over the length of the substrate tube or it varies.

[0027] After the deposition method is completed, the substrate tube remains in the composite material consisting of substrate tube and soot body and becomes part of the tubular quartz glass composite body to be produced (hereinafter also referred to as "quartz glass composite body" or simply "composite body"). The substrate tube consists of quartz glass and preferably has an inner diameter of at least 250 mm. The wall thickness of the substrate tube is preferably in the range of 4 mm to 10 mm and is therefore small in relation to its outer diameter.

[0028] The wall thickness is typically less than 20% of the outer diameter of the substrate tube. Thus, on the one hand, the substrate tube has a low weight, which reduces the dynamics of the rotational movement and facilitates handling and alignment, and on the other hand, the substrate tube has a low thermal mass, which keeps the heat dissipation and the formation of thermal stresses in the wall at a low level.

[0029] On the other hand, the wall thickness of the substrate tube is large enough to support a large volume of SiO2 soot body. Therefore, the wall thickness of the substrate tube is preferably at least 1% of the outer diameter of the substrate tube. The wall thickness "W S "(in mm) may also depend on the length of the substrate tube. Advantageously, the wall thickness also increases with increasing length of the substrate tube. Thus, WS may alternatively be set to the outer diameter D of the substrate tube. S function (in mm), taking into account the length of the substrate tube "L S ” (in mm), as follows: W S <0.2*(L S / 2,000mm)*D S .

[0030] After the outer deposition method and the optional dehydration of the soot body have been completed, the soot body is sintered (vitrified) according to method step (d), i.e. in the form of a composite material consisting of substrate tube and SiO2 soot body, i.e. connected to the substrate tube. The substrate tube used for this is characterized by a high thermal stability, so that during the sintering of the soot body, it becomes less soft than the soot body. The more thermally stable substrate tube gives the softened soot body a certain amount of support so that it achieves or maintains the desired cylindrical shape.

[0031] This is due to the fact that both the substrate tube and the soot body consist of SiO2 and therefore their coefficients of thermal expansion do not differ or do not differ significantly. The soot body is sintered onto the substrate tube, ensuring a certain adhesion in the composite material and preventing the soot body from detaching from the substrate tube during sintering.

[0032] The relatively high viscosity of the substrate tube is achieved, for example, in that over at least a portion of its length and / or over at least the thickness range of its wall, it consists of quartz glass which has a higher viscosity at the sintering temperature than the synthetic quartz glass of the soot body. In the simplest and preferred case, the substrate tube consists completely of quartz glass of the first quartz glass quality (i.e. quartz glass of higher viscosity). In a further, likewise preferred embodiment, the quartz glass of the substrate tube consists of quartz glass of higher viscosity only over a portion of its length (e.g. in the portion of its length which serves as a holder in the sintering furnace when sintering the soot body).

[0033] The sintering temperature is generally in the range of 1,200° C. to 1,450° C. It has proven useful if, at a measuring temperature of 1,350° C., the decimal logarithm of the viscosity of the first quartz glass quality is at least 0.25 lg (dPa*s), preferably at least 0.4 lg (dPa·s), particularly preferably at least 0.6 lg (dPa·s) higher than the decimal logarithm of the viscosity of the quartz glass of the second quartz glass quality. The viscosity difference is given here as the difference in the decimal logarithm lg (dPa·s) of the corresponding viscosity values. At the measuring temperature, the viscosity difference generally does not need to be greater than 1 lg (dPa·s).

[0034] The viscosity of quartz glass can be altered by hardening its glass network, in particular by dopants. The hardening of the glass network can be achieved by oxygen-deficient centers (also called "ODC centers"). Nitrogen, titanium oxide and aluminum oxide are suitable dopants for increasing the viscosity of quartz glass. In view of this, the preferred procedure provides that the aluminum oxide content of the quartz glass of the first quartz glass quality is at least 5 weight ppm, preferably at least 10 weight ppm higher than the aluminum oxide content in the quartz glass of the second quartz glass quality. Thus, in order to increase the viscosity, aluminum oxide can be added to quartz glass which is designed for use at high temperatures and is considered to have a certain temperature stability. The viscosity of synthetically produced quartz glass can also be increased in this way.

[0035] Naturally occurring quartz glass raw materials usually contain a certain amount of aluminum oxide. In view of this, quartz glass of the first quartz glass quality is preferably melted from naturally occurring raw materials. The costs for producing substrate tubes from natural quartz glass are relatively low. For example, such substrate tubes can be produced economically using the known crucible drawing method.

[0036] The quartz glass of the second quartz glass quality is, for example, high-purity, synthetically produced quartz glass which has no significant amount of aluminum oxide or has a small amount of aluminum oxide of less than 1 wt. ppm, preferably less than 0.5 wt. ppm.

[0037] In contrast, quartz glass of the first quartz glass quality preferably contains at least 5 wt. ppm, preferably at least 10 wt. ppm. However, aluminum oxide contents of more than 100 wt. ppm are generally not preferred.

[0038] The viscosity of the quartz glass can also be modified by hydroxyl groups. Hydroxyl groups can reduce the viscosity of the quartz glass. In view of this, the preferred procedure provides that the quartz glass of the first quartz glass quality has a hydroxyl group content of less than 30 wt ppm and preferably a hydroxyl group content of less than 20 wt ppm.

[0039] For example, by melting the raw materials in an electrically heated furnace or using a hydrogen-free plasma, hydroxyl group contents of less than 30 wt. ppm can be achieved in quartz glass qualities produced from natural raw materials. The hydroxyl group content of quartz glass produced synthetically via the SiO2 soot route can be adjusted to a large extent by drying the soot body before vitrification. By this drying process, low hydroxyl group contents in the range of a few wt. ppm can also be achieved in synthetically produced quartz glass, which are characterized by a relatively low viscosity. If desired, synthetic quartz glass low in hydroxyl groups is suitable as a substrate tube material, provided that the quartz glass of the soot body applied thereto has a relatively low viscosity.

[0040] In a preferred method, a substrate tube is used having a wall thickness in the range of 1.8 mm to 10 mm, preferably in the range of 4 mm to 8 mm.

[0041] The wall thickness is as large as possible in order to ensure the desired thermal stability. On the other hand, the wall thickness is as small as possible since material of the substrate tube is usually removed during further processing of the quartz glass composite.

[0042] The quartz glass composite body obtained after vitrification of this composite material consisting of substrate tube and SiO2 soot layer has an inner wall region consisting of first-quality quartz glass originating from the previous substrate tube. And the quartz glass composite body has an outer wall region consisting of second-quality quartz glass originating from the previous soot body. The thickness of the outer wall region is proportional to the wall thickness of the soot body and the soot density.

[0043] The soot density is usually in the range of 25% to 33% of the density of quartz glass. In view of this, the soot body obtained by the external deposition method is advantageously essentially cylindrical and preferably has a wall thickness which, after sintering the composite body, produces a glass layer with a layer thickness in the range of 25 mm to 100 mm, preferably in the range of 30 mm to 60 mm.

[0044] With regard to a tubular quartz glass composite body, the above-mentioned technical object is achieved according to the invention starting from a composite body of the type mentioned at the outset in that the blank wall comprises an inner wall region and an outer wall region, wherein the inner wall region at least partially consists of quartz glass of a first quartz glass quality and the outer wall region consists of quartz glass of a second quartz glass quality, wherein at a measuring temperature of 1,350° C. the viscosity of the first quartz glass quality is higher than the viscosity of the second quartz glass quality.

[0045] A tubular quartz glass composite body can be produced according to the invention using the above method. The outer wall region of the quartz glass composite body is optionally formed from quartz glass obtained by sintering a previous SiO2 soot body, and the inner wall region is formed from quartz glass of a previous substrate tube.

[0046] Since both the inner wall region and the outer wall region consist of quartz glass, their thermal expansion coefficients do not differ or do not differ significantly.During the preceding sintering, the soot body is sintered to the substrate tube, so that a certain adhesion in the composite body is ensured.

[0047] The relatively high viscosity of the inner wall region is achieved, for example, in that over at least a portion of its length and / or over at least a thickness range it consists of quartz glass which, at a measuring temperature of 1,350° C., has a higher viscosity than the synthetic quartz glass of the outer wall region.

[0048] It has proven useful if, at a measuring temperature of 1,350° C., the decimal logarithm of the viscosity of the first quartz glass quality is at least 0.25 lg (dPa·s), preferably at least 0.4 lg (dPa·s), particularly preferably at least 0.6 lg (dPa·s) higher than the decimal logarithm of the viscosity of the quartz glass of the second quartz glass quality. The viscosity difference is given here as the difference in the decimal logarithm lg (dPa·s) of the corresponding viscosity values. At the measuring temperature, the viscosity difference generally does not need to be greater than 1 lg (dPa·s).

[0049] The inner wall region may have a retaining element which during a previous sintering process enables suspension vitrification to form a quartz glass composite. In a preferred embodiment, the quartz glass of the inner wall region consists of higher-viscosity quartz glass only over a portion of its length (e.g. in the portion of its length where the retaining element is located).

[0050] In the simplest and particularly preferred case, the inner wall region consists completely of quartz glass of the first quartz glass quality, ie quartz glass of relatively high viscosity.

[0051] The viscosity of quartz glass can be altered by hardening its glass network, in particular by dopants. Hardening of the glass network can be achieved by oxygen-deficient centers (also called "ODC centers"). Nitrogen, titanium oxide and aluminum oxide are suitable dopants for increasing the viscosity of quartz glass.

[0052] In view of this, a preferred embodiment of the composite provides that the aluminum oxide content of the quartz glass of the first quartz glass quality is at least 5 wt. ppm, preferably at least 10 wt. ppm higher than the aluminum oxide content in the quartz glass of the second quartz glass quality. Thus, in order to increase the viscosity, aluminum oxide can be added to quartz glass which is designed for components that are used at high temperatures and are considered to have a certain temperature stability. The viscosity of synthetically produced quartz glass can also be increased in this way.

[0053] Naturally occurring quartz glass raw materials usually contain a certain amount of aluminum oxide. In view of this, quartz glass of the first quartz glass quality is preferably melted from naturally occurring raw materials. The cost of producing natural quartz glass is relatively low.

[0054] The quartz glass of the second quartz glass quality is, for example, high-purity, synthetically produced quartz glass which has no significant amount of aluminum oxide or has a small amount of aluminum oxide of less than 1 wt. ppm, preferably less than 0.5 wt. ppm.

[0055] In contrast, quartz glass of the first quartz glass quality preferably contains at least 5 wt. ppm, preferably at least 10 wt. ppm. However, aluminum oxide contents of more than 100 wt. ppm are generally not preferred.

[0056] The viscosity of the quartz glass can also be modified by hydroxyl groups. Hydroxyl groups can reduce the viscosity of the quartz glass. In view of this, a preferred embodiment of the composite provides that the quartz glass of the first quartz glass quality has a hydroxyl group content of less than 30 wt. ppm and preferably less than 20 wt. ppm.

[0057] For example, by melting the raw materials in an electrically heated furnace or using a hydrogen-free plasma, hydroxyl group contents of less than 30 wt. ppm can be achieved in quartz glass qualities produced from natural raw materials. The hydroxyl group content of quartz glass produced synthetically via the SiO2 soot route can be adjusted to a large extent by drying the soot body before vitrification. By this drying process, low hydroxyl group contents in the range of a few wt. ppm can also be achieved in synthetically produced quartz glass, which are characterized by a relatively low viscosity. If desired, synthetic quartz glass low in hydroxyl groups is suitable as a substrate tube material, provided that the quartz glass of the soot body applied thereto has a relatively low viscosity.

[0058] In a preferred embodiment of the composite body, the inner wall region consisting of first-quality quartz glass has a wall thickness in the range from 1.5 mm to 10 mm, preferably in the range from 4 mm to 8 mm.

[0059] The wall thickness is as large as possible to ensure the desired thermal stability. On the other hand, the wall thickness is as small as possible because the first quality quartz glass is usually removed during further processing of the composite.

[0060] In a preferred embodiment of the composite body, the outer wall region has a wall thickness in the range from 25 mm to 100 mm, preferably in the range from 30 mm to 60 mm.

[0061] By removing the inner wall region, for example by drilling, milling or etching, a hollow quartz glass cylinder is produced from the quartz glass composite body. The hollow quartz glass cylinder obtained in this way is used to produce etching rings for single-wafer plasma etching chambers or pressure vessels used in chemical process engineering.

[0062] The etched ring or pressure vessel has a specified target inner diameter. To produce the etched ring or pressure vessel, the composite is preferably used with an outer wall region having an inner diameter at least 1 mm smaller than the target inner diameter. The target inner diameter is adjusted by removing the entire inner wall region and excess portions on the outer wall region, wherein the excess portions are 1 mm or greater.

[0063] Definition and measurement methods

[0064] The various terms described above are further defined below. These definitions are part of the specification of the present invention. For terms and measurement methods that are not specifically defined in the specification, the interpretation according to the International Telecommunication Union (ITU) is relevant. In the event that one of the following definitions is inconsistent with the rest of the specification, the statement in this specification shall prevail.

[0065] Quartz glass tubular composite

[0066] The result of the deposition method is a tubular composite material consisting of a substrate tube made of quartz glass and a SiO2 soot body. The substrate tube defines the inner pores of the composite material. By sintering (vitrification) the soot body, a tubular composite body of quartz glass is obtained. By subsequently removing the substrate tube from the quartz glass composite body, a hollow quartz glass cylinder is obtained. The substrate tube is removed, for example, by drilling out. By mechanical, thermal or chemical further processing, a component of quartz glass is produced from the hollow quartz glass cylinder. Further mechanical processing includes drilling, sawing, cutting, milling, grinding, and polishing of inner and outer contours. Thermal further processing includes thermal drying, sintering, vitrification, melting, shaping and tempering. Further chemical processing includes doping and etching. The component of quartz glass is a ready-to-use quartz glass product or semi-finished product, for example a quartz glass hollow cylinder for producing a pressure vessel, or a quartz glass ring for producing a retaining ring for a wafer.

[0067] Quartz glass / synthetic quartz glass

[0068] Quartz glass is understood here to mean glass with a SiO2 content of at least 87% by weight. Quartz glass is undoped (SiO2 content = 100%) or contains dopants such as fluorine, chlorine, nitrogen, carbon, or oxides of boron, germanium, rare earth metals, aluminum, or titanium.

[0069] Quartz glass is, for example, a fusion product from a naturally occurring SiO 2 raw material (natural quartz glass), or it is produced synthetically (synthetic quartz glass), or consists of a mixture of these quartz glass types.

[0070] Sintering / vitrification

[0071] "Sintering" or "vitrification" here means a method step in which a porous silicon dioxide soot body is treated at high temperature in a furnace. Sintering / vitrification takes place in an inert gas, in an atmosphere containing hydrogen and / or helium or in a vacuum.

[0072] vacuum

[0073] The vitrification of the composite can be carried out under "vacuum". Negative pressure refers to absolute gas pressure. Vacuum refers to an absolute gas pressure of less than 50 mbar.

[0074] Base tube outer diameter / base tube inner diameter

[0075] The substrate tube cross section has a circular outer contour or an outer contour that deviates from a circular shape. If the outer contour deviates from a circular shape, the local "outer diameter value" is given by the diameter of the (smallest) circumference.

[0076] The substrate tube cross section has a circular inner contour or an inner contour that deviates from a circular shape. If the inner contour deviates from a circular shape, the local "inner diameter value" is given by the diameter of the (largest) inscribed circle.

[0077] In a longitudinal section of the substrate tube, the local value of the outer diameter may be constant or not constant over the entire length of the substrate tube. In the case of a constant outer diameter value, the substrate tube has a cylindrical shape when viewed from the outside. Non-constant outer diameter values ​​may vary over the entire length or over a portion of the length. The outer contour may vary, for example, continuously or gradually. In this case, the outer diameter results from the local outer diameter values ​​averaged over the entire length.

[0078] In a longitudinal section of the substrate tube, the local value of the outer diameter may be constant or not constant over the entire length of the substrate tube. In the case of a constant inner diameter value, the through-opening of the substrate tube is cylindrical. Non-constant inner diameter values ​​may vary over the entire length or over a portion of the length. The inner contour may vary, for example, continuously or gradually. In this case, the inner diameter results from the local inner diameter values ​​averaged over the entire length.

[0079] Viscosity

[0080] The "viscosity" of quartz glass is measured using a beam bending viscometer. The beam bending viscometry method covers 10 8 dPa·s to 10 15 dPa·s (in logarithmic units: 81 g (dPa·s) to 151 g dPa·s). The measuring device comprises a heatable three-point bending device with a measuring rod of the quartz glass to be measured (rod / strip: 50 mm long, 3 mm high, 5 mm wide). The variable measured is the deflection speed at the corresponding temperature.

[0081] Viscosity values ​​are also usually indicated using decimal logarithms in the form of lg (dPa·s) rather than exponential notation.

[0082] Softening temperature

[0083] Glasses cannot be assigned a specific softening temperature, but rather a softening temperature range. To determine the temperature values, reference is made here to the determination according to DIN ISO 7884 (1998), according to which the softening temperature is defined as the temperature at which the glass viscosity is 10 7.6 dPa·s (7.6 lg(dPa·s)). For the softening temperature of undoped quartz glass, temperature values ​​in the range of 1,600°C to 1,730°C are mentioned in the literature.

[0084] Exemplary embodiments

[0085] The present invention is explained in more detail below with reference to exemplary embodiments and patent drawings. In detail, in the schematic diagram,

[0086] Figure 1 shows a longitudinal section through a device for producing a composite body consisting of a substrate tube and a soot body in a first embodiment of a substrate tube holder,

[0087] Figure 2 A longitudinal section, partly in shear, of a device for producing a composite body consisting of a substrate tube and a soot body is shown in a second embodiment of a substrate tube holder.

[0088] Figure 3 Shows Figure 2 An enlarged view of a cross section of the substrate tube holder,

[0089] Figure 4 shows components of a zoned sintering furnace for vitrifying a composite body,

[0090] Figure 5 shows the vitrification of a vertical composite using a zoned sintering furnace,

[0091] Figure 6 The method steps for producing a first embodiment of a retaining edge on a substrate tube are shown.

[0092] Figure 7 Further method steps are shown for producing a retaining edge on a substrate tube.

[0093] Figure 8 shows the vitrification of a partially suspended composite using a first embodiment of a holding edge on a substrate tube in a zoned sintering furnace,

[0094] Fig. 9 The method steps of a second embodiment for producing a retaining edge on a substrate tube are shown.

[0095] Fig.10 Further method steps are shown for producing a retaining edge on a substrate tube.

[0096] Fig.11 shows an embodiment of a substrate tube having a retaining edge produced in a tapered form with its inner diameter prior to the external deposition process,

[0097] Fig.12 Shown in Figure 4 After the external deposition method is completed when the composite is vitrified in a zoned sintering furnace Fig.11 of the base tube, and

[0098] Fig.13 A longitudinal section through an exemplary embodiment of a tubular quartz glass composite body according to the invention is shown.

[0099] In the exemplary embodiments explained below, different substrate tubes are used, some of the properties of which are summarized in Table 1.

[0100] Table 1 - Base tube

[0101]

[0102] "Natural quartz glass" is produced from the melting of naturally occurring SiO2 raw materials (preferably in an electrically heated furnace). A particularly cost-effective production of substrate tubes consisting of natural quartz glass is carried out using the vertical crucible drawing method. Such quartz glass generally contains aluminum oxide in a concentration in the range of 6 to 18 ppm by weight and hydroxyl groups in a concentration of less than 50 ppm by weight. "Synthetic quartz glass" is obtained, for example, by flame hydrolysis or oxidation of synthetically produced silicon compounds, by polycondensation of organic silicon compounds according to the so-called sol-gel process, or by hydrolysis and precipitation of inorganic silicon compounds in a liquid. The viscosity of synthetic quartz glass depends on its composition, which can vary within wide ranges. In general, however, it can be said that synthetic quartz glass generally has a significantly lower viscosity than natural quartz glass.

[0103] Figure 1 The device schematically shown in Figure 1 is used for producing a large-volume composite material consisting of a substrate tube 1 and a SiO2 soot body 9. The device comprises a glass lathe 2 for holding and rotating the substrate tube 1 according to number 1 of Table 1. The substrate tube 1 has a left end face 1a, a right end face 1b, an outer side surface 1c, an inner side surface 1d, a horizontally oriented longitudinal axis 1e and a cylindrical through hole 1f. Adjacent to the front end 1a, there is a free substrate tube section 1g, on which reduced SiO2 soot particle deposition occurs during the soot deposition process. The free substrate tube section 1g can be formed as a holding edge during vitrification, which will be referred to below. Figure 4 and Figures 6 to 10 Explain in more detail.

[0104] The glass lathe 2 is represented by two oppositely disposed chucks 2a, 2b, wherein the chuck 2a is spring loaded, as indicated by the compression spring 2c. The compression spring 2c generates a pressure F which presses the two chucks 2a, 2b against each other, as indicated by the directional arrow 2d.

[0105] A hollow spindle 3a, 3b made of stainless steel is clamped in each of these chucks at the proximal end of the chucks 2a, 2b. Ideally, the axis of rotation of the hollow spindle 3a, 3b extends coaxially with the substrate tube longitudinal axis 1e. The hollow spindle 3a, 3b has an outer diameter of 90 mm and an inner diameter of 82 mm.

[0106] The distal ends of the hollow spindles 3a, 3b are pivotably connected to annular pressure plates 4a, 4b made of stainless steel. To this end, the distal ends of the hollow spindles 3a, 3b taper conically and are pressed against the corresponding pressure plates 4a, 4b due to the force of the spring 2c. Here, the conical ends protrude into the central holes of the corresponding annular pressure plates 4a, 4b and abut against the inner edges of the central holes.

[0107] The pressure plates 4a, 4b each adjoin a buffer disk 5a, 5b made of graphite, which in turn adjoin the substrate tube end faces 1a and 1b, respectively. The buffer disks 5a, 5b have a central hole, the diameter of which corresponds to the diameter of the pressure plates and extends coaxially therewith. The outer diameter of the pressure plates 4a, 4b is 10 mm smaller than the outer diameter of the substrate tube 1. The outer diameter of the buffer disks 5a, 5b extends beyond the outer diameter of the substrate tube 1 by 40 mm.

[0108] The total length of SiSiC is L Z A tubular centering support 6 having an outer diameter of 80 mm extends through the base tube through hole 1f and through the center holes of the pressure plates 4a, 4b and the buffer plates 5a, 5b. One end 6a of the centering support 6 is 500 mm long. a The hollow spindle 3a extends into the hollow spindle 3a and ends inside the hollow spindle, leaving a variable movement gap B of about 6 mm. a The other end 6b has a length L of 600 mm. b The hollow spindle 3b protrudes into the hollow spindle 3b and ends inside the hollow spindle, leaving a variable movement gap B of about 6 mm. b Therefore, the total movement gap B of the centering support 6 in the hollow main shaft 3a, 3b is z =B a +B b The outer diameter of the centering support 6 is constant over its length and is adapted to the inner diameter of the hollow spindles 3a, 3b in a clearance fit and can be displaced telescopically therein.

[0109] Three centering rings 7a, 7b, 7c made of graphite are placed on the centering support 6. The centering ring 7a is located in the area of ​​the left substrate tube end face 1a, the centering ring 7b is located in the area of ​​the right substrate tube end face 1b, and the centering ring 7c is located approximately in the middle of the substrate tube through hole 1f. All centering rings 7a, 7b, 7c have an outer diameter that matches the inner diameter of the substrate tube in a clearance fit, and they have an inner diameter that matches the outer diameter of the centering support in a clearance fit.

[0110] The end centering ring 7a, the buffer disk 5a and the pressure disk 4a are loosely connected to each other by screws 4c. The screws 4c have threads adjacent to the cylindrical part 4d. The threads are engaged in the internal threads in the pressure disk 4a in each case, so that the cylindrical part 4d is firmly against the pressure disk 4a in the tightened state. The length of the cylindrical part 4d is greater than the total thickness of the component stack of the centering ring 7a and the buffer disk 5a, so that the head of the screw 4c does not abut against the centering ring 7a, but there is a gap between the centering ring 7a and the screw head. In addition, the through hole for the cylindrical part 4d to pass through in the buffer disk 5a and the centering ring 7a is greater than the diameter of the cylindrical part 4d, so that the screw 4c can also be slightly tilted in the through hole. Therefore, this loose connection is suitable for allowing thermally induced length changes between the components of the substrate tube holder, and for compensating for deviations in the target size, positioning and alignment of the components. Furthermore, the screw 4c provides a certain torsional strength between the buffer disk 5a and the pressure disk 4a during the rotational movement of the substrate tube 1 and in this respect serves as a drive element for this rotational movement. The same applies to the connection of the centering ring 7b, the buffer disk 5b and the pressure disk 4b. For the purpose of thermal decoupling, a gap (not visible in the figure) is provided between the centering ring 7a, 7b and the buffer disk 5a, 5b.

[0111] Several deposition burners 8 for producing SiO2 particles are mounted on a common slide 8a, by means of which they can be moved reversibly and laterally along the outer surface 1c of the substrate tube 1 or along the formed SiO2 soot body 9, and can be moved perpendicularly to the outer surface, as indicated by the direction arrow 8b.

[0112] When Figure 2 and Figure 3 Use with Figure 1 When the same reference numerals are used throughout the text, these reference numerals represent the same or equivalent components or parts of the device.

[0113] Figure 2 The device schematically shown in Figure 1 The devices differ mainly in the type and nature of the substrate tube holder and substrate tube 21. Figure 1 The same reference numerals as in Figure 1 The same or equivalent parts or components of the device explained.

[0114] Substrate tube 21 corresponds to number 2 of Table 1. In the end region 21a, the inner diameter of the substrate tube has a circumferential constriction 26. The constriction 26 is produced before the start of the external deposition process, for example by locally softening the substrate tube 21 after clamping in the glass lathe 2. The constriction 26 is located at a distance of about 80 mm in front of the substrate tube end face. The inner diameter is 270 mm, except in the region of the constriction 26, in which the inner diameter is 250 mm.

[0115] The hollow spindles 23a, 23b are made of stainless steel and are each clamped with their proximal ends in a clamping chuck. Ideally, the axis of rotation of the hollow spindles 23a, 23b extends coaxially with the substrate tube longitudinal axis 1e. The hollow spindles 23a, 23b have an outer diameter of 100 mm. In the region of the distal ends of the hollow spindles 23a, 23b, a circumferential extension arm 2c is welded in each case.

[0116] The pivot connection between the hollow spindles 23a, 23b and the corresponding pressure plates 24a, 24 is designed here as a floating bearing and preferably comprises a universal ball-cone seat. Here, the distal ends of the hollow spindles 23a, 23b each form a convexly curved seat with a spherical or radius section, on which the pressure plate 24a or pressure plate 24b is movably mounted by having a concavely curved spherical or radius section that cooperates with the convexly curved seat.

[0117] Figure 3 An enlarged view of the pivotal connection between the hollow spindle 23a, 23b and the corresponding pressure plate 24a, 24b is shown. The end centering ring 7a, the buffer washer 5a and the pressure plate 24a form a stack of components that are loosely connected to each other by threaded screws 24c, which are each engaged in a thread in the extension arm 23c. The length of the cylindrical portion 24d is greater than the total thickness of the component stack consisting of the centering ring 7a, the buffer plate 5a and the pressure plate 24a. In addition, the width of the hole for receiving the screw 24c in the component stack is significantly greater than the diameter of the cylindrical portion 24d. This results in a number of gaps 25 being retained between the screw head 24e and the centering ring 7a and between the pressure plate 24 and the extension arm 23c, even in the case of a fixedly tightened threaded screw 24c, and along the cylindrical portion 24d. The gaps 25 ensure that the connection between the hollow spindle 23a, 23b and the corresponding pressure plate 24a, 24b remains pivotable. At the same time, the screw 24 c serves as a driving element for the rotational movement of the substrate tube 1 .

[0118] Reference below Figure 1 and Figures 4 to 10 An example of producing a quartz glass composite body is explained.

[0119] Soot deposition process

[0120] Oxygen and hydrogen are supplied as burner gases to the deposition burner 8, and a gas stream containing SiCl4 or another silicon-containing starting material is used as feed material for forming SiO2 particles. These components are converted into SiO2 particles in the associated burner flame, and these SiO2 particles are deposited on the substrate tube 1 rotating about the longitudinal axis 1e, thereby forming a soot body 9 from porous SiO2 soot.

[0121] In order to rotate the substrate tube 1, the glass lathe 2 transmits a torque to the hollow spindles 2a, 2b. At the same time, a pressure F acting in the axial direction is generated by the compression spring 2c, which presses the two hollow spindles 3a, 3b against each other and, depending on the offset of the spring relative to the spring rest length, is in the range between 0.5 kN and 10 kN. The pressure initially set is 1 kN and is applied to the pressure plates 4a, 4b, the buffer disks 5a, 5b and, therefore, also to the substrate tube end faces 1a, 1b. This pressure F creates a friction connection between the buffer disks 5a, 5b that is sufficient to hold the inherent weight of the substrate tube 1 and the weight of the soot body 9. The centering rings 7a, 7b, 7c serve only to prevent the substrate tube 1 from accidentally sliding or bending. The interaction of the hollow spindles 3a, 3b and the centering support 6 provides a certain amount of axial guidance, which compensates for any radial offset and angular differences between the axes of rotation of the hollow spindles 3a, 3b due to the presence of mechanical play and avoids mechanical stresses.

[0122] The deposition method is terminated as soon as the soot body 9 has reached a predetermined outer diameter, which, depending on the density of the soot layer, results in a predetermined outer diameter of the hollow cylindrical quartz glass composite body plus a margin of at least 1 mm. Given a soot density of approximately 30% (with reference to the density of quartz glass) and a target outer diameter of the quartz glass composite body of 362 mm, the outer diameter of the soot body is, for example, approximately 520 mm.

[0123] After the deposition method, the soot body 9 has a substantially barrel-like shape and extends to just before the ends on both sides of the substrate tube 1. The substrate tube section 1g protruding from the soot body 9 and only lightly covered with SiO2 soot has a length of approximately 100 mm.

[0124] Drying and vitrification process

[0125] The substrate tube 1 remains in the soot body 9. The composite material (1; 9) consisting of the substrate tube 1 and the soot body 9 is dehydrated in a drying furnace in an inert gas atmosphere, a halogen-containing atmosphere or in a vacuum. The soot body 9 is dried thermally by heating to a temperature of about 1,100° C. in a nitrogen atmosphere. By vitrifying the subsequently obtained dried SiO2 soot body in a vacuum, a synthetic quartz glass having the following properties is obtained:

[0126] Hydroxyl group content: about 200 ppm by weight,

[0127] Chlorine content: <0.2 ppm by weight,

[0128] 1. Viscosity at 350°C: 10.771 g (dPa·s).

[0129] The subsequent vitrification of the soot body 9 is carried out in a zoned sintering furnace with a vertically oriented substrate tube longitudinal axis 1 e under vacuum or in an atmosphere of gases that diffuse rapidly in quartz glass, such as helium and hydrogen, and therefore without the formation of bubbles. Figure 4 A cross section of such a zoned sintering furnace 40 is schematically shown. A furnace chamber 41 surrounds a furnace interior 42 in which an annular heating element 43 and a holding device 44 are located. This comprises a support rod 45 of fiber-reinforced carbon, the lower end of which is connected to a graphite platform 46. The upper end of the support rod 45 is held by a movable holder (not shown in the figure) and can be moved up and down by this. The support rod 45 extends through the annular opening of the heating element 43 and through a graphite cladding tube 47 standing upright on the platform 46.

[0130] The cladding tube ends are closed except for passages for support rods 45. The largely closed top and bottom 47a give the cladding tube 47 greater dimensional rigidity against external pressure compared to a cladding tube open on both sides.

[0131] During vitrification, the substrate tube 1 remains in the soot body 9. The holding device 44 is used to hold the composite material (1; 9) consisting of the substrate tube 1 and the soot body 9, the weight of which is supported on the platform 46 by the support rods 45. Figure 5 As schematically shown in FIG, the substrate tube 1 surrounds a cladding tube 47. Taking into account the higher thermal expansion coefficient of the graphite cladding tube 47 compared to the quartz glass substrate tube, the outer diameter of the cladding tube is adapted to the inner diameter of the substrate tube 1 so that the annular gap remaining during sintering is as small as possible and, for example, in the range of 1 mm to 10 mm, preferably less than 5 mm.

[0132] During vitrification, the heating element 43 is heated to a temperature of about 1,400° C. and the support rods 45 are continuously pulled upwards, so that the soot body 9 is vitrified from top to bottom. The composite material (1; 9) is shrunk onto the cladding tube 47 so that its outer diameter defines the lower limit of the inner diameter of the vitrified tubular quartz glass composite body. The substrate tube 1 consists of natural quartz glass, which has a higher viscosity at the sintering temperature than the synthetic quartz glass of the soot body 9. At a measuring temperature of 1,350° C., the viscosity difference corresponding to the difference in the decimal logarithms of the corresponding viscosity values ​​is about 0.51 g (dPa*s) [11.28 g (dPa*s) to 10.771 g (dPa*s)] according to Table 1.

[0133] Therefore, the substrate tube 1 is relatively thermally stable and does not deform or deforms slightly. This stabilizes the soot body 9 during vitrification. Specifically, the risk of the soot body 9 collapsing during vitrification and the formation of circumferential wrinkles, or widening of the inner diameter leading to waste, is offset.

[0134] After cooling, a tubular composite body with a thickness of about 41 mm is obtained from the substrate tube 1 and the glass layer, which is obtained by vitrification of the soot body 9. Despite the fact that the synthetic quartz glass shrinks onto the inner graphite cladding tube 47, it can be easily removed after vitrification, since graphite has a significantly higher thermal expansion coefficient than quartz glass and it shrinks more strongly when cooling.

[0135] The quartz glass of the substrate tube 1 can then be removed by mechanical treatment, for example by drilling.After grinding and smoothing the outer wall, a hollow quartz glass cylinder with an outer diameter of 360 mm and an inner diameter of 290 mm is obtained.

[0136] Comparative Example

[0137] As already mentioned above, the substrate tube 1 contributes to stabilization of the shape of the soot body 9 during vitrification due to its relatively high viscosity.

[0138] In order to examine the influence of the substrate tube 1 on the stabilization of the shape of the soot body 9, in a first comparative test, the substrate tube was removed before vitrification and only the soot body 9 was vitrified from top to bottom in the zoned sintering furnace 40. The soot body 9 collapsed under its own weight and the vitrified region detached from the cladding tube 47, which resulted in a local expansion of the inner diameter. The quartz glass tube produced in this way is unusable.

[0139] In a further comparative test, a substrate tube of synthetic quartz glass was used, the dimensions of which were identical to those of substrate tube 1, as specified by number 3 in Table 1. The viscosity of this quartz glass is lower than that of the quartz glass obtained by vitrification of the soot body 9. This shows that when such a composite is used, the cladding tube provides better adhesion to the vitrified soot body 9, so that the vitrified material does not detach over a large area. However, the weight of the vitrified upper region of the composite increases continuously, leading to compression towards the end of the process, so that the quartz glass tube produced in this way is ultimately unusable.

[0140] In a further comparative test, a substrate tube of synthetic quartz glass was used, the dimensions of which were identical to those of substrate tube 1, as specified by number 4 in Table 1. The viscosity of this quartz glass corresponds to the viscosity of the quartz glass obtained by vitrification of the soot body 9. However, it can also be seen here that when this composite material (1; 9) is sintered, compression occurs towards the end of the process, making the quartz glass tube produced in this way ultimately unusable.

[0141] Suspension vitrification

[0142] In order to counteract the compression effect of the inherent weight, a vitrification method is usually used in which the composite material (1; 9) does not stand permanently on the platform 46 during vitrification, but is at least temporarily suspended. This procedure, known for example from EP 0 701 975 B1, is referred to here as "suspension vitrification".

[0143] This ensures that the composite material (1; 9) remains suspended in the vitrification furnace from the outset, or that the holder of the composite material (1; 9) can be changed from an upright holder at the beginning of vitrification to a suspended holder during the vitrification process as soon as the inevitable axial sintering shrinkage becomes apparent. To achieve a suspended holder, measures can be taken on the substrate tube even before the outer deposition process is carried out. This can be done, for example, by shaping the substrate tube, or by a shaping process during the production of the substrate tube, such as by producing a constriction in the inner bore of the substrate tube during the drawing process of the substrate tube from the melt or of the mother tube to form the substrate tube. Alternatively or in addition and likewise preferably, these measures are generated "in situ" during vitrification.

[0144] A suitable measure for achieving suspended vitrification is to form a retaining edge on the substrate tube, which serves to ensure that the composite material (1; 9) is vitrified while at least temporarily suspended vertically (not just standing upright). Due to the at least temporary suspension retainer, in addition to the above-mentioned effect of thermally stabilizing the substrate tube 1, the compression of the soot body 9 is offset during vitrification, so that the soot body retains its desired geometry and waste is avoided.

[0145] For the suspension of the composite material (1; 9), for example, the substrate tube section 1g can be formed as a retaining edge during the vitrification of the soot body 9. Figures 6 to 10 Suitable methods for producing the holding edge "in situ" are explained in more detail.

[0146] Figure 6 A first method and device for the "in situ" production of a suspension body are schematically shown. A composite material (1; 9) consisting of a substrate tube 1 and a soot body 9 is introduced into a vitrification furnace 40 and supported by support rods 45 and a cladding tube 47 on a platform 46 with a vertically oriented soot body longitudinal axis 1e. An annular spacer 61 is placed on the upper end face 47a of the cladding tube 47, and a cone 62 in the form of an inverted cup is placed on the upper end face of the substrate tube 9. The spacer 61 and the cone 62 consist of graphite. The cone 62 has an inner cone 62a, which merges into a flat support surface 62b, in which a through hole 62c is present. In the initial state, the inner cone 62 rests on the outer side of the upper substrate tube section 1g. The support rod 45 extends through the through hole 62c and through the annular spacer 61.

[0147] The upper substrate tube section 1 g is formed as a suspension body during the vitrification process. Figure 7 The forming method is schematically shown in FIG. 4 . By means of the support rods 45, the upper substrate tube segment 1 g is moved far enough into the heating element 43, which is heated to the glass transition temperature, to soften it. Due to its weight, the cone 62 presses the soft upper substrate tube segment 1 g inwardly in the direction of the substrate tube longitudinal axis 1 e. The substrate tube segment 1 g rests on the inner cone 62 a and is thereby formed into an outer cone. As soon as the spacer 61 is in contact with the support surface 62 b of the cone 62, the forming method is completed.

[0148] During further vitrification, the composite body (1; 9) is heated in sections starting from its upper end. The composite body (1; 9) collapses continuously onto the graphite cladding tube 47 and also shrinks in length. The sintering shrinkage force is strong enough that the length of the substrate tube 1 is also shortened. However, the reduction in length is small.

[0149] In the first vitrification stage, the composite material ( 1 ; 9 ) stands upright on the platform 46 . Figure 8 The second vitrification stage is schematically shown. During this period, the previous substrate tube segment 1g, which has been shaped into an outer cone, emerges from the heating region of the heating element 43, cools and solidifies in the process. The inner side of this segment rests on the top side of the cladding tube 47a and then acts as a suspension 63 for the composite material (1; 9). Due to the length contraction, the segment is lifted from the platform 46 to form a narrow gap 48, which can then undergo further "suspended vitrification". This counteracts the collapse of the soot body 9, wherein the substrate tube 47 additionally stabilizes the shape of the resulting tubular quartz glass composite due to its higher viscosity.

[0150] Fig. 9 A second method and device for in-situ production of a suspension body, i.e. vitrification of a composite material (1; 9) consisting of a substrate tube 1 and a soot body 9 in one operation, is schematically shown. The composite material is introduced into a vitrification furnace 40 and supported by support rods 45 and a cladding tube 47 on a platform 46 with a vertically oriented soot tube longitudinal axis 1e. A ring 91 is placed on the upper end face 47a of the cladding tube 47, the ring consisting of two or more individual circular sectors 91a, 91b, which adjoin the central opening 91b of the ring and are mounted movably in the radial direction. A cone 92 made of graphite protrudes from above into the central opening 91b and has a conical shaft 92a and a cone head 92b with a flat underside. The ring 91 and the cone 92 consist of graphite. The outer diameter of the ring 91 corresponds approximately to the inner diameter of the substrate tube 1; the ring rests on the inner wall of the upper substrate tube section 1g. The diameter profile of the tapered shaft 92a is designed such that, in the initial state, the tapered shaft is immersed approximately halfway in the central opening 91b.

[0151] As the composite (1; 9) further vitrifies, the ridge 93 reaches the area above the heating element 43, cooling and solidifying in the process. The composite (1, 9) is heated in zones starting from its upper end, as described above with respect to the first method. In the first vitrification stage, the composite (1; 9) stands upright on the platform 46, and during the second vitrification stage, the ridge 93 serves as a holder for "suspended vitrification". The circular sector plate 91a protrudes from the inside into the ridge 93 and is fixed in the ridge in the vertical direction together with the substrate tube 1.

[0152] The length and inner diameter of the quartz glass composite body subsequently obtained are predetermined by the substrate tube 1. The preceding soot body forms a transparent synthetic quartz glass layer with a layer thickness of about 41 mm. After the quartz glass material has been removed from the substrate tube 1 and the outer wall has been ground and smoothed, a hollow quartz cylinder with an outer diameter of 360 mm and an inner diameter of 290 mm is obtained. Etching rings can thereby be cut for single-wafer plasma etching chambers and pressure vessels used in chemical process engineering.

[0153] For the production of etched rings or pressure vessels, preferably a composite body is used which has an outer wall region whose inner diameter is at least 1 mm smaller than the target inner diameter. The target inner diameter can be adjusted by mechanical or chemical treatment of the pores in the composite body.

[0154] Reference below Figure 2 and Figure 3 as well as Figures 11 to 13 Further exemplary embodiments of retaining edges for achieving suspended vitrification of a composite body (21, 9) are explained.

[0155] Soot deposition process

[0156] As mentioned above Figure 1 As explained, a soot separation method is performed. Fig.11 The substrate tube 21 used in this case is shown in longitudinal section. A previously produced constriction 26 is provided in the end region 21a. Figure 2 It can be seen that the soot body 9 is produced in such a way that it completely covers the constriction 26 . However, this measure is not absolutely necessary; the constriction can also be located completely outside the soot body 9 .

[0157] The deposition method ends as soon as the soot body 9 has reached a predetermined outer diameter: at a soot density of 30% (based on the density of quartz glass) and a target outer diameter of the quartz glass composite body of 362 mm, the soot body outer diameter is approximately 520 mm.

[0158] The composite material (21; 9) present after the soot separation process is subjected to a dehydration treatment in a chlorine-containing atmosphere at a temperature of 1,200° C. By vitrifying the subsequently obtained dried SiO2 soot body under vacuum, a synthetic quartz glass having the following properties is obtained:

[0159] Hydroxyl group content: <0.2 ppm by weight

[0160] Chlorine content: about 1,000 ppm by weight

[0161] 1. Viscosity at 350°C: 10.64 lg (dPa·s)

[0162] The composite material (21; 9) is then vitrified in a zoned sintering furnace 40 under vacuum. Fig.12 The composite material (21; 9) used in the zoned sintering furnace 40 is shown. During vitrification, the heating element 43 is heated to a vitrification temperature of about 1,400°C, and the support rods 45 are continuously pulled upwards, so that the soot body 9 is vitrified from top to bottom. The composite material (21; 9) shrinks onto the graphite cladding tube 47 so that its outer diameter defines the lower limit of the inner diameter of the vitrified quartz glass composite body. Since the substrate tube 21 consists of quartz glass, which has a higher viscosity than the quartz glass of the soot body 9 at the vitrification temperature, the substrate tube does not deform or deforms slightly, and stabilizes the soot body 9 during vitrification. Specifically, the risk of compression of the soot body 9 during vitrification and the formation of circumferential wrinkles, or widening of the inner diameter, is offset.

[0163] In the method stage shown, the vitrification process has progressed and a certain shrinkage of the soot body 9 has occurred. This means that the transition from the initial vitrification stage with upright composite material (21; 9) to "suspended vitrification" is complete. Due to the shrinkage of the soot body 9, the length of the substrate tube 21 has also shortened a little and the part has been slightly lifted from the platform 46, with the gap 98 being formed.

[0164] In an alternative procedure, the composite material ( 21 ; 9 ) remains suspended in the zoned sintering furnace from the outset, since the constriction 26 , which is already present before the soot separation process, bears against the upper edge of the graphite cladding tube 47 .

[0165] After cooling, the composite 100 ( Fig.13 ) is obtained from a substrate tube 21 and a glass layer 9a with a thickness of about 41 mm, the composite being obtained by vitrifying the soot body 9.

[0166] In the comparative test, a substrate tube of synthetic quartz glass was used, the dimensions of which were the same as those of the substrate tube 21, as designated by No. 3 in Table 1. The viscosity of this quartz glass was higher than the viscosity of the quartz glass obtained by vitrification of the soot body 9. More specifically, the decimal logarithm of the viscosity of this quartz glass at a measuring temperature of 1,350° C. was 0.131 g (dPa * s) higher than the decimal logarithm of the viscosity of the quartz glass obtained by vitrification of the soot body 9.

[0167] However, this viscosity difference proved to be too small to provide sufficient stability for the bulky and heavy substrate tube when sintering the composite body.

[0168] Fig.13 Shown along Figure 2 1 . A cross section of the composite body 100 obtained after vitrification in a view along the line A′-A″ drawn in FIG. 1 . The substrate tube 1 with the through-opening 1 f , the diameter constriction 26 and the synthetic quartz glass layer 9 a obtained after vitrification can be seen.

[0169] After removing the quartz glass material from the substrate tube 21 and grinding and smoothing the outer wall, a hollow quartz glass cylinder with an outer diameter of 360 mm and an inner diameter of 290 mm is obtained. Etching rings with corresponding inner and outer diameter values ​​(or with larger inner diameter and smaller outer diameter values) can be sawed out of this hollow quartz glass cylinder for holding semiconductor wafers in industrial single wafer plasma etching chambers or pressure vessels.

Claims

1. A method for producing a tubular quartz glass composite body in an external deposition method, comprising the following method steps: (a) providing a substrate tube, the substrate tube having a continuous through hole, a substrate tube outer diameter, a substrate tube inner diameter, a substrate tube wall thickness, a substrate tube outer surface and a substrate tube inner surface, wherein the continuous through hole extends coaxially with a longitudinal axis of the substrate tube, (b) rotating the base tube about a rotation axis extending coaxially or parallel to the longitudinal axis of the base tube, (c) depositing SiO2 particles on the outer surface of the substrate tube by means of at least one deposition burner to form a composite material (1 / 9; 21 / 9) consisting of the substrate tube and the SiO2 soot body, (d) sintering the composite material (1 / 9; 21 / 9) by heating at a sintering temperature to form the tubular quartz glass composite body (100), It is characterized in that A substrate tube is provided which at least partially consists of quartz glass of a first quartz glass quality, and the soot body consists of quartz glass of a second quartz glass quality, wherein the material-specific viscosity of the first quartz glass quality at the sintering temperature is higher than the material-specific viscosity of the second quartz glass quality.

2. The method according to claim 1, characterized in that At a measuring temperature of 1,350° C., the decimal logarithm of the viscosity of the first quartz glass quality is at least 0.251 g (dPa*s), preferably at least 0.41 g (dPa*s), particularly preferably at least 0.61 g (dPa*s) higher than the decimal logarithm of the viscosity of the quartz glass of the second quartz glass quality.

3. The method according to claim 1 or 2, characterized in that: The aluminum oxide content of the quartz glass of the first quartz glass quality is at least 5 wt. ppm, preferably at least 10 wt. ppm, higher than the aluminum oxide content of the quartz glass of the second quartz glass quality.

4. The method according to one or more of the preceding claims, characterized in that The quartz glass of the first quartz glass quality has a hydroxyl group content of less than 30 wt. ppm, preferably a hydroxyl group content of less than 20 wt. ppm.

5. Method according to one or more of the preceding claims, characterized in that The quartz glass of the first quartz glass quality is melted from naturally occurring raw materials.

6. Method according to one or more of the preceding claims, characterized in that The wall thickness of the substrate tube is in the range of 1.5 mm to 10 mm, preferably in the range of 4 mm to 8 mm.

7. Method according to one or more of the preceding claims, characterized in that The soot body is essentially cylindrical and has a wall thickness which, after sintering of the composite body, results in a glass layer having a layer thickness in the range from 25 mm to 100 mm, preferably in the range from 30 mm to 60 mm.

8. A tubular composite body of quartz glass having a length of at least 1,000 mm, a tube wall and having an inner diameter of at least 250 mm, characterized in that The blank wall comprises an inner wall region and an outer wall region, wherein the inner wall region at least partially consists of quartz glass of a first quartz glass quality and the outer wall region consists of quartz glass of a second quartz glass quality, wherein at a measuring temperature of 1,350° C. the viscosity of the first quartz glass quality is higher than the viscosity of the second quartz glass quality.

9. The composite body according to claim 8, characterized in that At a measuring temperature of 1,350° C., the decimal logarithm of the viscosity of the first quartz glass quality is at least 0.251 g (dPa*s), preferably at least 0.41 g (dPa*s), particularly preferably at least 0.61 g (dPa*s) higher than the decimal logarithm of the viscosity of the quartz glass of the second quartz glass quality.

10. The composite body according to claim 8 or 9, characterized in that The aluminum oxide content of the quartz glass of the first quartz glass quality is at least 5 wt. ppm, preferably at least 10 wt. ppm, higher than the aluminum oxide content of the quartz glass of the second quartz glass quality.

11. The complex according to one or more of claims 8 to 10, characterized in that The quartz glass of the first quartz glass quality is melted from naturally occurring raw materials.

12. The complex according to one or more of claims 8 to 11, characterized in that The inner wall region consisting of the first-quality quartz glass has a wall thickness in the range of 1.5 mm to 10 mm, preferably in the range of 4 mm to 8 mm.

13. The complex according to one or more of claims 8 to 12, characterized in that The outer wall region has a wall thickness in the range of 25 mm to 100 mm, preferably in the range of 30 mm to 60 mm.

14. Use of the tubular composite body according to one or more of claims 9 to 13 for producing an etching ring for semiconductor production or a pressure vessel, wherein a quartz glass hollow cylinder is produced by removing the inner wall region and the cylinder is processed into the etching ring or the pressure vessel.

15. Use according to claim 14, characterized in that The etched ring or the pressure vessel has a predetermined target inner diameter and, for producing the etched ring or the pressure vessel, a composite body is used which has an outer wall region having an inner diameter which is at least 1 mm smaller than the target inner diameter.

Citation Information

Patent Citations

  • Method for producing a hollow cylinder from quartz glass

    DE10064730A1

  • Manufacture of hollow cylinder of quartz glass using holder locates gas-impermeable synthetic quartz glass casing between holder and soot body

    DE10303290B3

  • Process for sintering hollow tubes of silica soot and support device therefor

    EP0701975A2

  • Process for sintering hollow tubes of silica soot and device for sintering such hollow tubes

    EP0701975B1

  • High purity synthetic silica and items such as semiconductor jigs manufactured therefrom

    US20130115391A1